The Effect of Word Discipline and Giving Rewards on Employee Performance at PT Inhutani I Banjarbaru, South Kalimantan - Karim, Abdul; Ahmad, Amrullah; Hawing, Hardianto (STIE Amkop Makassar, 2025)
This study aims to examine the effect of employee work discipline, and reward giving on employee performance at PT Inhutani I Banjarbaru, South Kalimantan. Sampling used a saturated sample, namely taking the entire population as a sample, a total of 30 employees working at PT.Inhutani I Banjarbaru, South Kalimantan. Data collection techniques through observation, questionnaires or questionnaires, and documentation. The analysis tool used was SPSS Version 125. The results showed that work discipline (X1) and reward (X2) both partially and simultaneously had a significant effect on employee performance (Y) at PT Inhutani I Banjarbaru South Kalimantan, as evidenced by the test results t (partial) work discipline variable which has a significant 0.002 <0.05 (α = 5%) and reward variable which has a significant 0.009 <0.05 (α = 5%). As well as work discipline and giving rewards together (Simultaneously) have a significant effect on employee performance at PT Inhutani I Banjarbaru, as evidenced by the results of the significance value of the F test output of 0.000 <0.05 (α = 5%).